Ardealite curing material, preparation method thereof and application of ardealite curing material in preparation of ardealite roadbed material
By using phosphogypsum curing materials composed of slag powder, electrolytic manganese slag and cement clinker, the slag powder-cement clinker system is stimulated for hydration reaction, and the problems of poor water resistance and low compressive strength of phosphogypsum roadbed fillers are solved, and efficient and stable phosphogypsum curing is achieved, promoting its large-scale application in the field of road engineering.
Patent Information
- Application Number
- CN202411932616.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-03-18
AI Technical Summary
Phosphate gypsum is a roadbed filler in highway construction, which has problems such as poor water resistance and low compressive strength, making it difficult to meet the requirements of roadbeds when carrying traffic loads, and the defects of existing curing technology limit their large-scale application.
The phosphogypsum curing material composed of slag powder, electrolytic manganese slag and cement clinker is used to stimulate the hydration reaction of the slag powder-cement clinker system through electrolytic manganese slag, forming a solidified body with high compressive strength and good water stability, achieving efficient curing of phosphogypsum.
The compressive strength and water stability of phosphogypsum roadbed fillers have been significantly improved, ensuring the stability and durability of curing effects, reducing the risk of secondary pollution, and promoting the large-scale and sustainable application of phosphogypsum in the field of road engineering.
Smart Images

Figure CN119638335A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a solidifying material, in particular to a phosphogypsum solidifying material, and also to a preparation method of the phosphogypsum solidifying material, and to an application of the phosphogypsum solidifying material in preparing a phosphogypsum roadbed material by consolidating phosphogypsum, belonging to the technical field of phosphogypsum solid waste resource utilization. Background Art
[0002] In the field of road engineering, with the continuous advancement of infrastructure construction, the demand for roadbed fillers continues to increase. As an industrial waste residue, phosphogypsum has a huge output. If it can be effectively used in roadbed construction, it will provide an ideal way for its large-scale and resource-based disposal, which has significant environmental and economic significance. However, when phosphogypsum is simply used as a roadbed filler, it faces many problems ("Current Status of Research on Recycling of Phosphogypsum in Highway Construction", Zong Wei et al., Building Materials World, 2022, 43(01):10-12). For example, phosphogypsum itself has poor water resistance, and its physical and mechanical properties will drop significantly after encountering water, resulting in unstable roadbed structure. In terms of compressive strength, its strength is relatively low, which makes it difficult to meet the requirements of roadbeds when bearing traffic loads. It is prone to deformation, cracking and other diseases, which seriously affect the service life and driving safety of the road.
[0003] In order to improve the performance of phosphogypsum to meet the requirements of roadbed fillers, phosphogypsum curing technology has become a research hotspot. At present, there are many studies on curing agents and curing materials for curing phosphogypsum. Existing phosphogypsum curing agents include many types: one is composed of precipitants (such as calcium oxide, calcium chloride, calcium hydroxide, etc.), net traps (such as sodium silicate, sodium aluminate, sodium cellulose acid, etc.), alkaline activators (such as sodium hydroxide, potassium hydroxide, sodium chloride, sodium sulfate, etc.) and slag high silicon aluminum solid waste (such as fly ash, steel slag, red mud, yellow phosphorus slag, etc.); the other is calcium carbonate, magnesium carbonate, and calcium hydroxide as curing agents. When the mass ratio of curing agent to phosphogypsum is 1:25, CaCO 3 +Ca(OH) 2 +MgCO 3 The solidification rates of the mixture for soluble phosphorus and fluorine in phosphogypsum are 70.11% and 96.79%, respectively. The phosphogypsum stabilized and solidified by the curing agent meets the national phosphogypsum emission standards ("Research on the composition design and solidification mechanism of geopolymer-solidified phosphogypsum roadbed filler", Li Heng, China University of Geosciences, 2022.DOI:10.27492 / d.cnki.gzdzu.2022.000308.).
[0004] However, there are still many shortcomings in the existing research on these phosphogypsum curing agents or curing materials, and only a very small amount of research focuses on the development of solid waste-based curing materials. In terms of coagulation and hardening characteristics, there is a general problem of slow coagulation and hardening speed ("Performance Research and Engineering Application of High-Dosage Phosphogypsum Roadbed Filler", Li Dandan, et al., New Building Materials, 2024, 51(11):55-61), and it is difficult to form a stable and high-strength curing structure. The combination of solid waste materials alone has limited improvement in compressive strength. Even after treatment, the compressive strength of phosphogypsum roadbed filler is still difficult to fully meet the long-term high-standard use requirements of road engineering. Some solid waste-based curing materials may also cause secondary pollution, causing potential harm to surrounding soil, water bodies and other environmental media, violating the original intention of environmental protection, and bringing additional environmental governance costs and ecological risks. In summary, although the existing phosphogypsum has potential in the application of road subgrade materials, the defects of existing curing technology limit its large-scale application. Summary of the invention
[0005] In view of the large demand for fillers in road subgrade construction, the use of phosphogypsum as roadbed filler has technical difficulties such as poor water resistance and low strength when used in large dosages. The first purpose of the present invention is to provide a phosphogypsum solidifying material, which can be used for phosphogypsum consolidation to significantly improve the compressive strength, water stability and other properties of the phosphogypsum roadbed filler, ensure the stability and durability of the solidification effect, reduce the risk of secondary pollution, and promote the large-scale and sustainable application of phosphogypsum in the field of road engineering. The solidifying material uses industrial solid waste such as slag powder and electrolytic manganese slag as the main raw materials, thereby realizing the resource recycling of solid waste.
[0006] The second object of the present invention is to provide a method for preparing phosphogypsum solidifying materials. The preparation method uses industrial solid waste as the main raw material, has low cost, high solid waste resource utilization rate, and the preparation method is simple, does not require complicated processes and special equipment, is easy to implement in industrial production, and can quickly and efficiently produce a large amount of phosphogypsum solidifying materials to meet the large demand for fillers in road subgrade construction, realize the resource utilization of large amounts of phosphogypsum, and facilitate large-scale production.
[0007] The third object of the present invention is to provide a method for preparing phosphogypsum roadbed materials. This method, by using a new type of phosphogypsum curing material, can significantly improve the compressive strength, water stability and other properties of the phosphogypsum roadbed materials, thereby broadening the application scope of the phosphogypsum roadbed materials in the field of infrastructure construction.
[0008] In order to achieve the above technical objectives, the present invention provides a phosphogypsum solidification material, which comprises slag powder, electrolytic manganese slag and cement clinker.
[0009] The phosphogypsum solidifying material of the present invention mainly uses electrolytic manganese slag as an activating material, which is used to activate slag powder and cement clinker to undergo a hydration reaction to form a solid body with high compressive strength and good water stability. The slag powder mainly contains calcium oxide and active Al 2 O 3 and SiO 2 In terms of components, cement clinker mainly provides calcium oxide alkaline components and active silicates. For the slag powder-cement clinker system, if electrolytic manganese slag is not used as the excitation material, the hydration products produced by conventional excitation are mainly calcium carbonate, calcium silicate, etc. The main chemical components of electrolytic manganese slag are active silicon dioxide and sulfate. The use of electrolytic manganese slag to perform sulfate excitation on the slag powder-cement clinker system mainly forms hydration products such as calcium vanadate, calcium sulfide calcium silicate, calcium sulfide calcium manganese ore, among which calcium vanadate and calcium sulfide calcium manganese ore are both calcium sulfide calcium vanadate crystals, which provide good strength support for the consolidated body. The mechanism of using electrolytic manganese slag to excite the slag powder-cement clinker system can be divided into the following two parts: Part I: In the electrolytic manganese slag-cement clinker-slag powder system, the OH released by the hydration reaction - Can make soluble Mn 2+ Converted into insoluble Mn(OH) 2 or MnO 2 , OH - It can also react with ammonium salt in electrolytic manganese slag to release ammonia. Part II: In the electrolytic manganese slag-cement clinker-slag powder system, the electrolytic manganese slag combines well with the hydration products of cement clinker and slag powder to generate a large amount of C-(A)-SH gel, calcium vanadium, etc., and the Ca in the C-(A)-SH generated by the hydration reaction 2+ Can replace Mn 2+ , while Al in calcium vanadium 3+ Can also replace Mn 2+ , so that the heavy metals in EMR can be stably solidified. At the same time, AFm generated by the conversion of calcium vanadate can also adsorb pollutants. In addition, phosphogypsum solidification materials are mainly used to solidify phosphogypsum. Not only does the mechanical properties of the formed consolidated body meet the requirements of roadbed materials, but also pollutants such as free phosphate and fluoride ions contained in the phosphogypsum are effectively fixed, effectively preventing secondary pollution. The slag powder-cement clinker system of the phosphogypsum solidification material contains a large amount of active calcium components, which can mineralize the fluoride ions in the phosphogypsum into calcium fluoride, while the electrolytic manganese slag contains free ammonium and active magnesium oxide, and the slag powder also contains active magnesium oxide, which can mineralize the free phosphate in the phosphogypsum into stable ammonium magnesium phosphate (struvite) during the hydration reaction, realizing the synergistic solidification of pollutants such as ammonium and phosphate, and avoiding secondary pollution.
[0010] As a preferred solution, the slag powder, the electrolytic manganese slag and the cement clinker are composed of the following mass percentages: 70-90% slag powder, 6-20% electrolytic manganese slag and 4-14% cement clinker. The components in the phosphogypsum solidifying material of the present invention need to be controlled in a coordinated manner. The slag powder is the main component, which contains calcium oxide and active Al 2 O 3 and SiO 2 Components, in which CaO reacts with water to form Ca(OH) 2 , which not only provides an alkaline environment for the subsequent hydration reaction, but also 2 O 3 and SiO 2 The volcanic ash reaction occurs to generate xCaO·Al 2 O 3 ·yH 2 O and CSH, and these hydration products can further react with CaSO 4 The components undergo hydration reaction to generate calcium sulfonite, which can improve the microstructure and porosity of the consolidated body. Slag powder accelerates the hydration reaction and provides hydration space, making the hydration products evenly distributed and thus improving the compactness of the solidified soil. The hydration reaction generates calcium sulfonite and CSH gel, which give the consolidated body excellent physical and mechanical properties. As the main component of phosphogypsum solidifying material, further increasing the content of slag powder will affect the dosage of phosphogypsum, and at the same time will reduce the solidification time of the solidified material, which is not conducive to engineering construction. If its content is too low, it is not enough to cause a volcanic ash reaction. Electrolytic manganese slag mainly provides active SiO 2 And sulfate is used to stimulate the slag powder-cement clinker system, and ammonium ions and active magnesium oxide are provided to solidify the free phosphate in the phosphogypsum. If the dosage of electrolytic manganese slag is too low, it will affect the hydration reaction product and reduce the strength of the solid body. At the same time, the free phosphate in the phosphogypsum cannot be effectively fixed. When the dosage of electrolytic manganese slag is too high, it will cause the system to slow down early and reduce the early compressive strength because it contains a certain amount of dihydrate gypsum and calcium vanadate. Cement clinker mainly contains silicate and calcium oxide components, which can provide an alkaline environment and active silicates. Active silicates and calcium oxide form cementing materials in an alkaline environment. If the dosage is too high, alkali efflorescence is likely to occur, and the solid body will expand and crack in the later stage. If the dosage is too low, the pH of the system will not meet the reaction conditions. The main hydration reactions of the phosphogypsum solidifying material of the present invention during the solidification of phosphogypsum are as follows:
[0011] CaO+H 2 O=Ca(OH) 2
[0012] Al 2 O 3+xCa(OH) 2 +yH 2 O=xCaO·Al 2 O 3 ·yH 2 O
[0013] 2CaO+SiO 2 +mH 2 O=CS-H+CCa(OH) 2
[0014] 3CaO·Al 2 O 3 6H 2 O+3(CaSO 4 ·2H 2 O)+20H 2 O=3CaO·Al 2 O 3 ·3CaSO 4 ·32H 2 O
[0015] As a preferred solution, the slag powder includes at least one of granulated blast furnace slag, copper tailings, and lead-zinc smelting slag. The preferred slag powder has main chemical components of calcium oxide (CaO), silicon dioxide (SiO 2 ) and aluminum oxide (Al 2 O 3 ), specifically from various metallurgical waste slags, which are mainly pyrometallurgical slags, which contain calcium oxide, silicon dioxide and aluminum oxide with high reactivity, such as granulated blast furnace slag, copper tailings, lead-zinc smelting slag, etc., which are ground into powder. The most preferred slag powder is granulated blast furnace slag.
[0016] As a more preferred solution, the specific surface area of the slag powder is 300 to 800 m 2 / kg, and the moisture content is not higher than 5%. The specific surface area of slag powder is controlled at 300~800m 2 / kg range, it can ensure that it has sufficient contact area with other raw materials and phosphogypsum, and promote the hydration reaction. The moisture content is not higher than 5% to prevent the active substances in the slag powder from prematurely undergoing hydration reaction and deactivation. Controlling the performance parameters of the slag powder within a suitable range can effectively play the role of the slag powder in the solidification material.
[0017] As a preferred solution, the sulfate content of the electrolytic manganese slag is 15-30%, and the pH is in the range of 5-6. The electrolytic manganese slag is the acidic waste residue produced in the electrolytic manganese process, and its main chemical components are silicon dioxide (SiO 2) and sulfate, which are mainly used as stimulating materials. When the sulfate content in the electrolytic manganese slag is too low, it cannot provide enough sulfate ions to participate in the hydration reaction, affecting the strength of the solidified material; when the sulfate content is too high, because it contains a certain amount of dihydrate gypsum and calcium vanadate, it will cause the system to slow down early setting and reduce the early compressive strength. The pH range of 5 to 6 is determined based on the chemical properties of the electrolytic manganese slag and the acid-base balance requirements in the entire consolidation system. Within this pH range, the electrolytic manganese slag can better cooperate with other raw materials, promote beneficial reactions, and ensure the stable performance of the solidified material.
[0018] As a preferred solution, the phosphogypsum solidifying material further comprises a silicon regulator; the mass of the silicon regulator is 6-20% of the total mass of slag powder, electrolytic manganese slag and cement clinker. As a more preferred solution, the silicon regulator comprises metakaolin. In a slightly acidic environment, Al-O in metakaolin is + The fracture occurs and Al 3+ ,PO 4 3- The intermediate units such as -Si-OP- are then obtained through polycondensation to obtain a three-dimensional network of aluminum phosphate phase gel, which can achieve the cementation of fine-grained phosphogypsum and enhance the compressive properties of phosphogypsum consolidation materials. The introduction of metakaolin is mainly to adjust the silicon-aluminum ratio, and further optimize the silica (SiO 2 ) by mass content ≥50%. Since slag powder is a high-calcium system, after the slag powder is introduced into the system, kaolin is used to adjust the silicon-aluminum ratio. When the silica content reaches this range, a stable grid structure can be formed in the system, effectively activating the system and improving the compressive strength of the consolidated body. If the silica content is insufficient, it may lead to an imperfect grid structure and affect the overall performance of the solidified material. When the silicon regulator is increased to 12% of the total mass of slag powder, electrolytic manganese slag and cement clinker, there is no further improvement in the compressive strength of the consolidated body. Therefore, the mass of the silicon regulator is further preferably 6 to 12% of the total mass of slag powder, electrolytic manganese slag and cement clinker.
[0019] The optimal formula of the phosphogypsum solidifying material of the present invention is (mass percentage composition): 70-90% granulated blast furnace slag powder, 6-20% electrolytic manganese slag, 4-14% cement clinker, and 6-12wt.% metakaolin.
[0020] The present invention also provides a method for preparing the phosphogypsum solidifying material, which comprises mixing, ball milling, drying and grinding raw materials including slag powder, electrolytic manganese slag and cement clinker in sequence to obtain the phosphogypsum solidifying material.
[0021] As a preferred solution, the ball milling conditions are: the ball milling rate is 300-400 r / min, and the time is 1-2.5 h. The ball milling can refine the particle size of the raw materials and improve the reaction activity.
[0022] As a preferred solution, the drying conditions are: 40-80° C., and drying for 12-36 hours. The moisture content is reduced by drying to avoid premature hydration reaction.
[0023] The present invention also provides a method for preparing phosphogypsum roadbed materials, comprising the steps of uniformly mixing the phosphogypsum solidifying material and the phosphogypsum, adding water and stirring to form a slurry, and then pressing the slurry into shape through a mold, demolding the slurry, and curing the slurry.
[0024] As a preferred solution, the mass percentage composition of the phosphogypsum solidifying material and the phosphogypsum is 5-45%:55-95%. A large number of experiments have shown that when the amount of phosphogypsum solidifying material is higher than 45%, the utilization rate of phosphogypsum is significantly reduced, and it is impossible to achieve the application of large amounts of phosphogypsum; when the amount of phosphogypsum solidifying material is lower than 5%, the compressive strength gradually decreases as the amount decreases. This is because excessive phosphogypsum may cause problems such as uneven internal structure and increased porosity, and it is impossible to meet the 7d unconfined compressive strength road base standard of cement stabilized materials. Therefore, the selected solidifying material should not only ensure the effective utilization of phosphogypsum, but also enable the material to achieve better strength performance. The mass percentage composition of the phosphogypsum solidifying material and the phosphogypsum is further preferably 20-40%:60-80%.
[0025] As a preferred solution, the amount of water added is 25-35% of the total mass of the phosphogypsum solidifying material and the phosphogypsum.
[0026] Compared with the prior art, the technical solution of the present invention has the following beneficial technical effects:
[0027] 1) The phosphogypsum solidifying material of the present invention makes full use of multiple industrial solid wastes such as slag powder and electrolytic manganese slag as main raw materials. This combination mode of multiple solid wastes gives full play to the synergistic effect of "treating waste with waste", and no new hazardous waste is generated, the conditions are mild, and it is conducive to large-scale production.
[0028] 2) The phosphogypsum solidifying material of the present invention gives full play to the synergistic effect among slag powder, electrolytic manganese slag, metakaolin, etc., which not only solves the problems of strength and water resistance of phosphogypsum roadbed materials, but also can realize the efficient stabilization of harmful components such as heavy metals, ammonium, phosphate, fluoride ions, etc. in solid wastes such as electrolytic manganese slag and phosphogypsum, thereby avoiding secondary pollution.
[0029] 3) The phosphogypsum solidifying material of the present invention has a good effect in consolidating phosphogypsum, and can be flexibly formulated for different types of phosphogypsum (such as different impurity contents, different crystal forms, etc.), and the prepared phosphogypsum roadbed material can meet the special requirements of various projects for roadbed filler strength, stability and construction performance, which greatly broadens the application scope of phosphogypsum in the field of road engineering and improves the universality of its resource utilization.
[0030] 4) In the production process of the phosphogypsum solidifying material of the present invention, the multi-solid waste raw materials used are mostly wastes in the industrial production process, which realizes the recycling of wastes and reduces the demand for the exploitation of natural resources. At the same time, due to the simple preparation process and the absence of energy-intensive steps such as high-temperature calcination, compared with the production of traditional solidifying materials, energy consumption is greatly reduced, thereby effectively reducing carbon emissions caused by energy production. In the construction process, the roadbed filler prepared by the solidifying material has excellent performance. During transportation, mixing, compaction and other processes, due to its good workability and compaction characteristics, it can reduce the use time and power consumption of machinery, further reduce energy consumption and carbon emissions during construction, and reflect significant environmental protection and sustainable development advantages. BRIEF DESCRIPTION OF THE DRAWINGS
[0031]
Figure 1
[0032]
Figure 2
[0033]
Figure 3
[0034]
Figure 4
[0035] The present invention is further described below in conjunction with specific embodiments, but the protection scope of the present invention is not limited thereto.
[0036] In the following specific examples and comparative examples, the main components of phosphogypsum and various solidifying material raw materials are shown in Table 1:
[0037] Table 1 Main components and contents of solid waste raw materials (wt.%)
[0038]
[0039] The preparation method of the phosphogypsum solidified material in Examples 1 to 14 is as follows: slag powder, electrolytic manganese slag and cement clinker are sieved and mixed in proportion, and then put into a ball mill at a rate of 350 r / mins for 1.5 h, and dried in an oven at 60° C. for 24 h. The solidified material is dried by ball milling and cooled to room temperature.
[0040] The cement clinker involved in the embodiment is a common model P.O42.5 on the market. The leaching and detection methods involved refer to the "Solid Waste Leaching Toxicity Leaching Method Horizontal Oscillation Method" (HJ 557-2010), "Water Quality Total Phosphorus Determination Ammonium Molybdate Spectrophotometric Method" (GB 11893-89), "Soil Water-soluble Fluoride and Total Fluoride Determination Ion Selective Electrode Method" (HJ873-2017).
[0041] The granulated blast furnace slag, copper tailings, and lead-zinc smelting slag involved in the embodiment are pre-treated by grinding and drying, and the specific surface area is about 500m 2 / kg, and the moisture content is about 4%.
[0042] The ammonia nitrogen leaching concentration in the electrolytic manganese slag involved in the embodiment is 301 mg / L.
[0043] The leaching concentrations of fluorine and phosphorus in the phosphogypsum involved in the embodiment are 200.54 mg / L and 153.21 mg / L respectively.
[0044] The XRD patterns of the lead-zinc smelting slags involved in the following examples are as follows: Figure 4 shown.
[0045] Example 1
[0046] This example is used as a control experiment: cement clinker is directly used as the solidifying material.
[0047] The phosphogypsum dried at 60°C in an oven and cement clinker were mixed in a ratio of 9:1 in a cement slurry mixer and stirred at low speed for 150 seconds. After standing still, 30% tap water was added and stirred rapidly for 150 seconds before stopping the machine. The stirred sample was placed in a forming mold, and the mold was pressed into shape on a universal testing machine. The mold was then demolded with a hydraulic electric demolding device, and then cured in a constant temperature and humidity curing box for 7 days (temperature of 20°C, relative humidity of 90%). After the curing was completed, an unconfined compressive strength test was performed with a universal testing machine. The test results of three parallel experiments are shown in Table 2. The microstructure is as follows: Figure 3 As shown in a.
[0048] Example 2
[0049] This example is a condition exploration experiment: it mainly examines the influence of different types of slag powder on the compressive strength of the solidified material after consolidation.
[0050] The solidified material (containing 84% granulated blast furnace slag powder, 6% electrolytic manganese slag, and 10% cement clinker) dried in an oven at 60°C was stirred at low speed in a cement slurry mixer for 150 seconds. After standing still, 30% tap water was added, and then the machine was stopped after rapid stirring for 150 seconds. The stirred sample was placed in a forming mold, and the mold was placed on a universal testing machine for pressing and forming. Then, the mold was demolded with a hydraulic electric demolding device, and then cured in a constant temperature and humidity curing box for 7 days (temperature of 20°C, relative humidity of 90%). After the curing was completed, an unconfined compressive strength test was performed with a universal testing machine. The test results of three parallel experiments are shown in Table 2. The microstructure is as follows: Figure 3 As shown in b.
[0051] Example 3
[0052] This example is a condition exploration experiment: This example mainly examines the influence of different types of slag powder on the compressive strength of the solidified material after consolidation.
[0053] The solidified material (containing 84% copper tailings powder, 6% electrolytic manganese slag, and 10% cement clinker) dried in an oven at 60°C was stirred at low speed in a cement slurry mixer for 150 seconds. After standing still, 30% tap water was added, and then the machine was stopped after rapid stirring for 150 seconds. The stirred sample was placed in a forming mold, and the mold was pressed into shape on a universal testing machine. Then, it was demolded with a hydraulic electric demolding device, and then cured in a constant temperature and humidity curing box for 7 days (temperature of 20°C, relative humidity of 90%). After the curing was completed, an unconfined compressive strength test was performed with a universal testing machine. The test results of three parallel experiments are shown in Table 2. The microstructure is as follows: Figure 3 As shown in c.
[0054] Example 4
[0055] This example is a condition exploration experiment: it mainly examines the influence of different types of slag powder on the compressive strength of the solidified material after consolidation.
[0056] The solidified material (containing 84% lead-zinc smelting slag, 6% electrolytic manganese slag, and 10% cement clinker) dried in an oven at 60°C was stirred at low speed in a cement slurry mixer for 150 seconds. After standing still, 30% tap water was added, and then the machine was stopped after rapid stirring for 150 seconds. The stirred sample was placed in a forming mold, and the mold was placed on a universal testing machine for pressing and forming. Then, the mold was demolded with a hydraulic electric demolding device, and then cured in a constant temperature and humidity curing box for 7 days (temperature of 20°C, relative humidity of 90%). After the curing was completed, an unconfined compressive strength test was performed with a universal testing machine. The test results of three parallel experiments are shown in Table 2. The microstructure is as follows: Figure 3 As shown in middle d.
[0057] Example 5
[0058] This embodiment is a condition exploration experiment: it mainly examines the influence of different electrolytic manganese slag dosages on the compressive strength of the solidified material after consolidation.
[0059] The solidified material (containing 78% granulated blast furnace slag powder, 12% electrolytic manganese slag, and 10% cement clinker) dried in an oven at 60°C was stirred at low speed in a cement slurry mixer for 150 seconds. After standing still, 30% tap water was added, and then the machine was stopped after rapid stirring for 150 seconds. The stirred sample was placed in a forming mold, and the mold was placed on a universal testing machine for pressing and forming. Then, the mold was demolded with a hydraulic electric demolding device, and then cured in a constant temperature and humidity curing box for 7 days (temperature of 20°C, relative humidity of 90%). After the curing was completed, an unconfined compressive strength test was performed with a universal testing machine. The test results of three parallel experiments are shown in Table 2. The microstructure is as follows: Figure 3 As shown in figure e.
[0060] Example 6
[0061] This embodiment is a condition exploration experiment: it mainly examines the influence of different electrolytic manganese slag dosages on the compressive strength of the solidified material after consolidation.
[0062] The solidified material (containing 66% granulated blast furnace slag powder, 24% electrolytic manganese slag, and 10% cement clinker) dried in an oven at 60°C was stirred at low speed for 150 seconds in a cement slurry mixer. After standing still, 30% tap water was added, and then the machine was stopped after rapid stirring for 150 seconds. The stirred sample was placed in a forming mold, and the mold was placed on a universal testing machine for pressing and forming. Then, the mold was demolded with a hydraulic electric demolding device, and then cured in a constant temperature and humidity curing box for 7 days (temperature of 20°C, relative humidity of 90%). After the curing was completed, an unconfined compressive strength test was performed with a universal testing machine. The test results of three parallel experiments are shown in Table 2. The microstructure is as follows Figure 3 As shown in figure f.
[0063] Example 7
[0064] This embodiment is a condition exploration experiment: it mainly examines the influence of different kaolin dosages on the compressive strength of the solidified material after consolidation.
[0065] The solidified material (containing 84% granulated blast furnace slag powder, 6% electrolytic manganese slag, 10% cement clinker, and 6% metakaolin) dried in an oven at 60°C was stirred at low speed in a cement slurry mixer for 150 seconds. After standing still, 30% tap water was added, and then the machine was stopped after rapid stirring for 150 seconds. The stirred sample was placed in a forming mold, and the mold was placed on a universal testing machine for pressing and forming. Then, it was demolded with a hydraulic electric demolding device, and then cured in a constant temperature and humidity curing box for 7 days (temperature of 20°C, relative humidity of 90%). After the curing was completed, an unconfined compressive strength test was carried out. The test results of three parallel experiments are shown in Table 2. The microstructure is as follows Figure 3 As shown in g.
[0066] Example 8
[0067] This example is a condition exploration experiment: it mainly examines the effect of different kaolin dosages on the compressive strength of the solidified material after consolidation:
[0068] The solidified material (containing 84% granulated blast furnace slag powder, 6% electrolytic manganese slag, 10% cement clinker, and 12% metakaolin) dried in an oven at 60°C was stirred at low speed for 150 seconds in a cement slurry mixer. After standing still, 30% tap water was added, and then the machine was stopped after rapid stirring for 150 seconds. The stirred sample was placed in a forming mold, and the mold was placed on a universal testing machine for pressing and forming. Then, it was demolded with a hydraulic electric demolding device, and then cured in a constant temperature and humidity curing box for 7 days (temperature of 20°C, relative humidity of 90%). After the curing was completed, an unconfined compressive strength test was carried out. The test results of three parallel experiments are shown in Table 2. The microstructure is as follows: Figure 3 As shown in h.
[0069] Example 9
[0070] This embodiment is a condition exploration experiment: it mainly examines the influence of different kaolin dosages on the compressive strength of the solidified material after consolidation.
[0071] The solidified material (containing 84% granulated blast furnace slag powder, 6% electrolytic manganese slag, 10% cement clinker, and 24% metakaolin) dried in an oven at 60°C was stirred at low speed for 150 seconds in a cement slurry mixer, and 30% tap water was added after it was still. After rapid stirring for 150 seconds, the machine was stopped and the stirred sample was placed in a forming mold. The mold was placed on a universal testing machine for compression molding, and then demolded with a hydraulic electric demoulder. After that, it was cured in a constant temperature and humidity curing box for 7 days (temperature of 20°C, relative humidity of 90%). After the curing was completed, an unconfined compressive strength test was carried out. The test results of three parallel experiments are shown in Table 2.
[0072] Table 2 Compressive strength of the cured materials of Examples 1 to 9 after consolidation (MPa)
[0073] Experimental Group An experiment Secondary experiment Three experiments average value Example 1 1.02 1.89 1.65 1.52 Example 2 15.62 14.32 13.44 14.46 Example 3 7.89 7.63 6.32 7.28 Example 4 6.32 5.21 5.79 5.77 Example 5 10.02 9.58 9.89 9.83 Example 6 10.02 9.58 9.89 9.89 Example 7 17.99 18.59 18.65 18.41 Example 8 20.21 17.63 19.25 19.03 Example 9 20.56 18.32 18.26 19.04
[0074] From Table 2 we can see that:
[0075] Example 1 directly uses cement clinker to solidify phosphogypsum, and the formed consolidated body 7D unconfined compressive strength is about 1.52 MPa, which meets the application requirements of Class II and below highways, medium and light traffic, and subbase specified in JTGT F20-2015.
[0076] Examples 2 to 9 respectively investigated the effects of different types of slag powder, different amounts of electrolytic manganese slag and different amounts of kaolin on the compressive strength of the consolidated body, indicating that the application effect of granulated blast furnace slag powder is better than that of copper tailings powder, and that the addition of electrolytic manganese slag should not be too high, which will reduce the strength of the consolidated body. The introduction of an appropriate amount of kaolin can significantly improve the strength of the consolidated body.
[0077] Example 10
[0078] This example mainly examines the effect of different curing material dosages on the compressive strength of phosphogypsum consolidation body:
[0079] The solidified material dried in an oven at 60°C (containing 84% granulated blast furnace slag powder, 6% electrolytic manganese slag, 10% cement clinker, and 6% metakaolin) and phosphogypsum were stirred at a low speed in a cement slurry mixer at a ratio of 4:6 for 150 seconds, and then 30% tap water was added after standing, and then stirred rapidly for 150 seconds and then stopped. The stirred sample was placed in a forming mold, and the mold was pressed and formed on a universal testing machine, and then demolded with a hydraulic electric demolding device, and then cured in a constant temperature and humidity curing box for 7 days (temperature of 20°C, relative humidity of 90%). After the curing was completed, an unconfined compressive strength test was carried out; the solidified material dried in an oven at 60°C was sampled and cured according to the above ratio. After curing to the 6th day, one group was placed in an oven at 60°C for drying for 24 hours, and one group was placed in water for immersion for 24 hours. After completion, an unconfined compressive strength test was carried out using a universal testing machine to obtain a ratio of immersion strength / drying strength, which was the softening coefficient. The test results of three parallel experiments are shown in Table 3.
[0080] Through the phosphorus and fluorine leaching experiment of the solid body, it was found that the phosphorus solidification rate was 89.91% and the fluorine solidification rate was 93.82%.
[0081] Embodiment 11
[0082] This example mainly examines the effect of different curing material dosages on the compressive strength of phosphogypsum consolidation body:
[0083] The solidified material dried in an oven at 60°C (containing 84% granulated blast furnace slag powder, 6% electrolytic manganese slag, 10% cement clinker, and 6% metakaolin) and phosphogypsum were stirred at a low speed in a cement slurry mixer at a ratio of 3:7 for 150 seconds, and then 30% tap water was added after standing, and then stirred rapidly for 150 seconds and then stopped. The stirred sample was placed in a forming mold, and the mold was pressed and formed on a universal testing machine, and then demolded with a hydraulic electric demolding device, and then cured in a constant temperature and humidity curing box for 7 days (temperature of 20°C, relative humidity of 90%), and an unconfined compressive strength test was performed after the curing was completed; the solidified material dried in an oven at 60°C was sampled and cured according to the above ratio, and after curing to the 6th day, one group was placed in an oven at 60°C for drying for 24 hours, and one group was placed in water for immersion for 24 hours. After completion, an unconfined compressive strength test was performed using a universal testing machine to obtain a ratio of immersion strength / drying strength, which is the softening coefficient. The test results of three parallel experiments are shown in Table 3.
[0084] Through the phosphorus and fluorine leaching experiment of the solid body, it was found that the phosphorus solidification rate was 88.26%; the fluorine solidification rate was 90.64%.
[0085] Example 12
[0086] This example mainly examines the effect of different curing material dosages on the compressive strength of phosphogypsum consolidation body:
[0087] The solidified material dried in an oven at 60°C (containing 84% granulated blast furnace slag powder, 6% electrolytic manganese slag, 10% cement clinker, and 6% metakaolin) and phosphogypsum in a ratio of 2:8 were stirred at low speed in a cement slurry mixer for 150 seconds, and then 30% tap water was added after standing, and then stirred rapidly for 150 seconds and then stopped. The stirred sample was placed in a forming mold, and the mold was placed on a universal testing machine for compression forming, and then demolded with a hydraulic electric demolding device, and then cured in a constant temperature and humidity curing box for 7 days (temperature of 20°C, relative humidity of 90%), and an unconfined compressive strength test was performed after the curing was completed; the solidified material dried in an oven at 60°C was sampled and cured according to the above ratio, and after curing to the 6th day, one group was placed in an oven at 60°C for drying for 24 hours, and one group was placed in water for immersion for 24 hours. After completion, an unconfined compressive strength test was performed using a universal testing machine to obtain a ratio of immersion strength / drying strength, which is the softening coefficient. The test results of three parallel experiments are shown in Table 3.
[0088] Through the phosphorus and fluorine leaching experiment of the solid body, it was found that the phosphorus solidification rate was 87.45% and the fluorine solidification rate was 90.32%.
[0089] Example 13
[0090] This example mainly examines the effect of different curing material dosages on the compressive strength of phosphogypsum consolidation body:
[0091] The solidified material dried in an oven at 60°C (containing 84% granulated blast furnace slag powder, 6% electrolytic manganese slag, 10% cement clinker, and 6% metakaolin) was mixed with phosphogypsum in a ratio of 1:9 in a cement slurry mixer at low speed for 150 seconds, and then 30% tap water was added after standing, and then quickly stirred for 150 seconds and then stopped. The mixed sample was placed in a forming mold, and the mold was placed on a universal testing machine for compression forming, and then demolded with a hydraulic electric demolding device, and then cured in a constant temperature and humidity curing box for 7 days (temperature of 20°C, relative humidity of 90%). After the curing was completed, an unconfined compressive strength test was carried out. The solidified material dried in an oven at 60°C was sampled and cured according to the above ratio. After curing to the 6th day, one group was placed in an oven at 60°C for drying for 24 hours, and one group was placed in water for immersion for 24 hours. After completion, an unconfined compressive strength test was carried out using a universal testing machine. The ratio of the water immersion strength / drying strength obtained was the softening coefficient. The test results of three parallel experiments are shown in Table 3.
[0092] Through the phosphorus and fluorine leaching experiment of the solid body, it was found that the phosphorus solidification rate was 87.89% and the fluorine solidification rate was 90.09%.
[0093] Table 3 Compressive strength of phosphogypsum consolidation bodies with different curing material dosages in Examples 10 to 13 (MPa)
[0094] Experimental Group An experiment Secondary experiment Three experiments average value Example 10 5.63 4.09 5.13 4.95 Embodiment 11 5.15 3.50 4.25 4.30 Example 12 3.00 2.89 1.76 2.55 Example 13 1.25 2.31 0.95 1.50 Pure phosphogypsum 0.65 0.71 0.89 0.75
[0095] From Table 3 we can see that:
[0096] In Examples 10 to 13, the phosphogypsum curing material is directly used to achieve the 7D unconfined compressive strength of the solidified body formed by the curing of the phosphogypsum, which is about 1.50 to 4.95 MPa. Among them, the curing material of Example 13 has similar performance to 100% cement clinker, and the solidified bodies formed after curing the phosphogypsum meet the application requirements of Class II and below highways, medium and light traffic, and subbases specified in JTGT F20-2015. In Examples 10 to 12, by appropriately adjusting the proportion of the phosphogypsum curing material, the compressive strength of the solidified body formed is relatively high, which meets the application requirements of most highway bases and subbases.
[0097] Table 4 Unconfined compressive strength standard R of cement stabilized materials at 7D age 4 (MPa)
[0098]
Claims
1. A phosphogypsum solidifying material, characterized in that: Contains slag powder, electrolytic manganese slag and cement clinker.
2. The phosphogypsum solidifying material according to claim 1, characterized in that: The slag powder, the electrolytic manganese slag and the cement clinker are composed according to the following mass percentages: 70-90% slag powder, 6-20% electrolytic manganese slag and 4-14% cement clinker.
3. A phosphogypsum solidifying material according to claim 1 or 2, characterized in that: The slag powder includes at least one of granulated blast furnace slag, copper tailings, and lead-zinc smelting slag.
4. The phosphogypsum solidifying material according to claim 3, characterized in that: The specific surface area of the slag powder is 300 to 800 m 2 / kg, and the moisture content is not higher than 5%.
5. A phosphogypsum solidifying material according to claim 1 or 2, characterized in that: The electrolytic manganese slag has a sulfate mass content of 15-30%, and a pH value in the range of 5-6.
6. A phosphogypsum solidifying material according to claim 1, 2 or 4, characterized in that: It also contains silicon conditioners; and / or, The mass of the silicon regulator is 6-20% of the total mass of the slag powder, the electrolytic manganese slag and the cement clinker.
7. The phosphogypsum solidifying material according to claim 6, characterized in that: The silicon conditioning agent includes metakaolin.
8. The method for preparing a phosphogypsum solidified material according to any one of claims 1 to 7, characterized in that: The raw materials including slag powder, electrolytic manganese slag and cement clinker are mixed, ball-milled, dried and ground in sequence to obtain the product.
9. A method for preparing phosphogypsum roadbed material, characterized in that: The phosphogypsum solidifying material according to any one of claims 1 to 7 is uniformly mixed with phosphogypsum, and then water is added and stirred to form a slurry. The slurry is pressed into shape by a mold, demolded, and cured.
10. The method for preparing a phosphogypsum roadbed material according to claim 9, characterized in that: The mass percentage composition of the phosphogypsum solidifying material and the phosphogypsum is 5-45%:55-95%; and / or, the amount of water added is 25-35% of the total mass of the phosphogypsum solidifying material and the phosphogypsum.